STUDENT INITIATED DEPARTURES FROM THE INITIATION-RESPONSE-FEEDBACK (IRF) FORMAT - Natalya V. Vesnina (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article presents the results of a study of interactions in a second language classroom. Using Conversation Analysis as the primary method of scientific inquiry the author investigates the student initiated departures from the Initiation-Response-Feedback (IRF) format claimed to be predominant in the educational contexts. The segment of the lesson analyzed in the present article is the “homework check” segment which traditionally initiates the lesson and is an example of a teacher-fronted classroom activity meaning that the time classroom interaction was unrolling in a very structured way. Still, the students were systematically finding ways of taking control over what is happening and reshaping interactional patterns in terms of content, form and participants of the classroom speech events. In particular, the students were actively self-selecting as the next speakers when not invited to speak by the teacher and using the turn allocated within IRF structure of interaction in order to stir the current interaction in the direction that couldn’t be planned or predicted by the teacher. This dynamism, however, seems dependent not only on the teacher’s willingness to sometimes “give the floor” to students but to level of agency exhibited by students. They raised questions and initiated discussions which ultimately contribute to deeper understanding of the grammatical phenomena studied and, through personal agency, position themselves as active participants in the learning process. Thus, it is demonstrated that departures from IRF create an alternative universe in which inferences, hypotheses, assumptions and expectations about language use are shared, explored, analyzed, adopted or discarded and it is this highly collaborative communicative process that provides second language learners with support and resources for further learning as well as opportunities of naturalistic conversation.